Exploring the Determinants of Undergraduate and Graduate Students Satisfaction with College Management (SADGAMAYA, 2026)
Understanding the determinants of student satisfaction with college management is vital for improving the educational experience. This study investigates undergraduate and postgraduate students' satisfaction regarding academic support, campus facilities, extracurricular activities, professional development opportunities, and career and mentorship support. Data were collected from 1,014 students across colleges in Nepal, domestic and foreign-affiliated universities, including Purbanchal University, Far-Western University, Tribhuvan University, Pokhara University, Gandaki University, Lincoln University College Malaysia, HELP University Malaysia, and Asia Pacific University of Technology and Innovation. The study highlights how these factors influence satisfaction levels and offers actionable insights for institutions. By addressing gaps in quality management and student satisfaction, this research provides a foundation for enhancing institutional performance. Identifying ways to optimize these components can improve student outcomes, retention rates, and overall success, contributing to better educational experiences and institutional metrics.